Integrating agency and resource dependence theories to examine the impact of corporate governance and innovation on firm performance - Farheen Akram; Muhammad Abrar Ul Haq (Cogent Business & Management, 2022)
This study aimed to investigate the mediating role of innovation between corporate governance and firm performance. The theoretical foundations of this study were the agency and resource dependence theories. The data were collected from annual reports of non-financial firms listed on the Pakistan Stock Exchange and spanned the period from 2010 to 2019. The direct impact of corporate governance was evaluated using Driscoll Kraay's standard errors, while for the mediating role of innovation, each indirect impact was separately examined using the bootstrapping technique in Stata. Interestingly, the study found significant support for a direct impact of corporate governance variables on firm performance, except for independent directors. The indirect impact of corporate governance on firm performance was also appraised, except for directors' interlocks and family ownership. Based on the findings, the study suggests that firms can achieve higher performance by effectively using embedded resources from the corporate governance structure and innovation.
Keywords: 650; corporate governance; firm performance; innovation; mediation; Pakistan stock exchange